Cloning and in silico investigation of a putative voltage-gated calcium channel gene and protein in Astacus leptodactylus - Saglam Berk; Ergin Bora; Beyatli Nazlı Coskun; Arslan Kaan; Bastug Turgut; Purali Nuhan (Türk Biyokimya Dergisi, 2023)
Voltage-gated calcium channels are essential elements in development of many cellular processes like electrical signaling, contraction secretion and gene expression. There has been a fair amount of information about the functional and structural properties of the calcium channels in mammalian species. Crayfish serves as a model animal for many types of experiments. However, there has been no information related to the molecular and genetic properties of the calcium channels in the crayfish.